Tax policy and income inequality in the US, 1979-2007 - Olivier Bargain; Mathias Dolls; Herwig Immervoll; Dirk Neumann; Andreas Peichl; Nico Pestel; Sebastian Siegloch (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
We assess the effects of U.S. tax policy reforms on inequality by applying a new decomposition method allowing us to disentangle the policy effect from changing market incomes. Over the period 1979-2007, the cumulative policy effect aggravated inequality by increasing the income share of the top 20% in contrast to the middle class' share. The tax policy effect accounts for up to 29% of the total change in inequality; its contribution increases up to 41% if we take into account behavioral responses. While Republican policymakers increased inequality especially at the top, Democrats increased the income share of the bottom 80%.
urn:nbn:de:bsz:180-madoc-354560
Keywords: H23; H31; H53; P16; 330; Tax policy; Inequality; Redistribution; Partisan Politics; Political Economy